Role of p53 in Anticancer Drug Treatment- and Radiation-Induced Injury in Normal Small Intestine - Shi Jin (Cancer Biology & Medicine, 2012)
In the human gastrointestinal tract, the functional mucosa of the small intestine has the highest capacity for absorption of nutrients and rapid proliferation rates, making it vulnerable to chemoradiotherapy. Recent understanding of the protective role of p53-mediated cell cycle arrest in the small intestinal mucosa has led researchers to explore new avenues to mitigate mucosal injury during cancer treatment. A traditional p53 inhibitor and two other molecules that exhibit strong protective effects on normal small intestinal epithelium during anticancer drug treatment and radiation therapy are introduced in this work. The objective of this review was to update current knowledge regarding potential mechanisms and targets that inhibit the side effects induced by chemoradiotherapy.